2007
DOI: 10.1111/j.1365-2958.2007.05849.x
|View full text |Cite
|
Sign up to set email alerts
|

The novel transcriptional regulator SczA mediates protection against Zn2+stress by activation of the Zn2+‐resistance geneczcDinStreptococcus pneumoniae

Abstract: SummaryMaintenance of the intracellular homeostasis of metal ions is important for the virulence of many bacterial pathogens. Here, we demonstrate that the czcD gene of the human pathogen Streptococcus pneumoniae is involved in resistance against Zn 2+ , and that its transcription is induced by the transition-metal ions Zn 2+ , Co 2+ and Ni 2+ . Upstream of czcD a gene was identified, encoding a novel TetR family regulator, SczA, that is responsible for the metal ion-dependent activation of czcD expression. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
169
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(176 citation statements)
references
References 71 publications
7
169
0
Order By: Relevance
“…Metal analysis demonstrated that total Zn content was increased within activated macrophages infected with the fungal pathogen Histoplasma capsulatum (78). This was the result of increased Zn import via the ZIP2 importer, but the Zn ion was then distributed to intracellular Decreased survival [70] organelles such as the Golgi apparatus via Zn transporters ZnT4 and ZnT7 or bound to metallothionein (78). By contrast, LPS binding to the TLR4 receptor does not trigger Zn import into the macrophage.…”
Section: Alterations In Host Cu and Zn Status In Response To Bacteriamentioning
confidence: 98%
See 1 more Smart Citation
“…Metal analysis demonstrated that total Zn content was increased within activated macrophages infected with the fungal pathogen Histoplasma capsulatum (78). This was the result of increased Zn import via the ZIP2 importer, but the Zn ion was then distributed to intracellular Decreased survival [70] organelles such as the Golgi apparatus via Zn transporters ZnT4 and ZnT7 or bound to metallothionein (78). By contrast, LPS binding to the TLR4 receptor does not trigger Zn import into the macrophage.…”
Section: Alterations In Host Cu and Zn Status In Response To Bacteriamentioning
confidence: 98%
“…They typically consist of a transcriptional response regulator paired with the Zn efflux transporter, although there may be some redundancies in these exporters. The best exemplified Zn export systems in the literature are the ZntR/ZntA regulator/P-type ATPase Zn efflux system in E. coli (68,69) and the GczA (SczA)/CzcD regulator/cation diffusion facilitator system in S. pyogenes and S. pneumoniae (70,71).…”
Section: The Role Of Bacterial Cu and Zn Detoxification Systems In VImentioning
confidence: 99%
“…Two TFRs, SczA and ComR, bind metals, but the molecular details of these interactions are not known (71,72). Further structural studies will provide clues as to the mechanisms surrounding how TFRs specifically recognize metal ions.…”
Section: Figmentioning
confidence: 99%
“…A small number of TetR family regulators have been characterized for LAB, among which only S. pneumoniae SczA has so far been implicated in a stress response. Resistance against zinc in S. pneumoniae depends mostly on the CzcD transporter, whose expression is under the control of SczA and whose activity is Zn 2ϩ dependent (82). Despite extensive studies on other TetR regulators, metal-binding TetR regulators are quite uncommon in bacteria and await further characterization (68).…”
Section: One-component Systemsmentioning
confidence: 99%